Beyond the modern age: an archaeology of contemporary culture - Goudzwaard, B. (InterVarsity Press, 2017)
Starting with our students' experiences -- The archaeology of modernity -- The classical modern worldview -- The structural and cultural critiques of modernity -- Modern ideologies and the postmodern worldview -- Evaluating modernity's four worldviews -- Transcendence and modernity: resources for moving beyond modernity -- Meaning from outside: reengagement with religion? -- Culture and religion: Philip Reiff's sacred sociology -- Becoming human: desire, violence, and René Girard -- Modernity, pluralism, and God -- The starving Christ and a preferential option for the poor -- Finding ways beyond modernity -- Engaging the contemporary crisis -- Ways forward for economic life and global climate change -- Bob Goudzwaard's faith-filled witness in politics.